Gardening lab for kids : 52 fun experiments to learn, grow, harvest, make, play, and enjoy your garden - Brown, Renata Fossen (Quarry Books, 2014)
"A source of ideas to help children learn how to grow their own garden encourages families to enjoy nature and features fifty-two creative plant-related activities set into weekly lessons."